Special issue law firms, legal culture, and legal practice - Sarat, Austin (Studies in law, politics, and society ;, 2010)
Large law firms have become a dominant feature of the legal landscape in the United States and elsewhere. This volume of Studies in Law, Politics, and Society examines the situation of large law firms. The articles collected here address the following questions: How has the large law firm altered, or adapted to, the ideals/ideology of the legal profession? How do law firms function as organizations? What happens to firms when they globalize their practices? What is the situation of scholarship on large law firms? Has the firm been incorporated into boarder interdisciplinary configurations? What, if any,new paradigms ofstudy of firms areon the horizon?.